ANALISIS PROGRAM KEGIATAN DALAM PERCEPATAN PEMULIHAN SEKTOR EKONOMI - Raihan Nashif; Ifat Fadhlurrahman (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The Surakarta City Medium-Term Development Plan (RPJMD) for 2021-2026 proclaims a development vision for the next 5 years, namely "MAKING SURAKARTA AS A CULTURAL CITY THAT IS MODERN, RESISTANT, ABILITIES, CREATIVE AND PROSPEROUS". One of the explanations for this vision is how the City of Surakarta and all elements within it can be Creative. Creative Cities will make the creative sector a driving force for economic growth. Several aspects that support the application of the creative city concept are creative industries, creative communities, creative environments and events. In this case creative is also directed at the development of the economic sector in society so that it will have an impact on increasing the economic competitiveness of the City of Surakarta in the form of increasing Local Own Revenue.